Optimalisasi Penanaman Tanaman Obat Keluarga dengan Pupuk Organik dan Pemantauan Kualitas Pupuk - Prabowo, Muhammad Iqbal Bagus; Risqi, Annisa Miftahul; Nitara, Kalika Rhea; Yogyantoro, Alifia Putri; Ruhil , Seruni; Al-Ishlah, Rizal Diaz; Firmansyah, Maulana Erdio; Pratiwi, Ananda Kartika Sela; Pramana, Muhammad Alif; Rasyid, Muhammad Haikal; Widowaty, Yeni (Universitas Muhammadiyah Yogyakarta, 2025)
Family Medicinal Plants (TOGA) are types of plants that have many benefits as natural herbal medicines and can be cultivated independently in the household environment. The use of TOGA is not only beneficial for health, but can also improve the nutritional quality of the family, and provide economic benefits by making it a commodity that can be sold. However, many people still have difficulty in optimizing TOGA cultivation, especially in the use of the right fertilizer to increase agricultural yields. This Community Service Program aims to improve skills and optimize TOGA planting on land owned by Women Farmers Groups (KWT) with an approach based on environmentally friendly agriculture. One of the efforts made is the use of quality organic fertilizers that can increase soil fertility without causing negative impacts on the environment. In addition, monitoring the quality of fertilizers using fertilizer measuring tools is also applied to ensure efficient use of fertilizers and in accordance with plant needs. This activity includes socialization of the benefits of TOGA as well as planting medicinal plants, training in the manufacture and use of liquid organic fertilizers, and the application of simple technology to monitor the quality of the fertilizers used. The results of this activity show an increase in the understanding and skills of KWT members in sustainable TOGA cultivation. KWT members now understand better how to care for and manage TOGA plants using more environmentally friendly organic fertilizers. In addition, there is an increase in TOGA plant productivity thanks to the use of more controlled fertilizers. Thus, this program is expected to encourage environmentally friendly agriculture, improve community welfare, and have a positive impact on the surrounding environment